Redox-dependent substrate-cofactor interactions in the Michaelis-complex of a flavin-dependent oxidoreductase - Tobias Werther (Nature Portfolio, 2017)
Due to their transient nature, enzyme-substrate complexes are difficult to characterize structurally. Here, the authors capture the reactive reduced form of xenobiotic reductase A bound to its substrate and show that the oxidation state of the flavin cofactor affects the interaction of the substrate with the enzyme.